The sacroiliac joint – Victim or culprit. Issue 1 (February 2019) - Booth, James; Morris, Samuel
Abstract: It is estimated that 10–30% of all low back pain is attributed to the sacroiliac joints. There are many challenges to diagnosing and treating the sacroiliac joints. Central to this challenge is determining whether the sacroiliac joint is the primary source of pain or dysfunction. This paper considers the complexities of diagnosis and management of sacroiliac joint dysfunction by providing a best evidence informed overview of the mechanics of the sacroiliac joint, the aetiology of sacroiliac joint dysfunction and the most current diagnostic strategies and management options for dysfunctions of these joints from a biopsychosocial perspective. This comprehensive chapter aims to shed light on the challenges of managing sport and exercise-related sacroiliac joint pain, and in so doing highlight the paucity of high quality research investigation of the joint, and the clinical uncertainty that is an unavoidable feature of addressing dysfunction of this joint.